Effect of trisodium citrate in the treatement of mastitis in cattle - Sindhu O K (Department of Clinical Medicine, College of Veterinary and Animal Sciences, 2003)
A study was conducted in the Department of Clinical Medicine, College of Veterinary and Animal Sciences, Mannuthy, for a period of three semesters during the year 2002 and 2003, to assess the efficacy of oral administration oftri- sodium citrate as therapeutic agent in subclinical mastitis of cattle and as a supportive treatment along with antibiotic in clinical mastitis of cattle and to evaluate the levels of pH, citric acid, calcium, lactose and chloride in milk of cattle affected with mastitis. Twenty cases of subclinical mastitis and fifteen cases of clinical mastitis were utilized for the study. Subclinical mastitis cases were divided in to three groups and clinical mastitis cases divided into two groups based on the therapeutic trial adopted. Gram positive cocci were isolated from cases in which the milk appeared white, cream, slight yellow or yellow coloured with fine clots or flakes. Gram negative coccobacilli were isolated from cases in which the milk appeared straw or yellow coloured watery milk with clots or without clots. Gram positive cocci were isolated from majority of the subclinical and clinical mastitis cases than the gram negative coccobacilli. Gram positive cocci were, highly sensitive to enrofloxacin, cephotaxime and ciprofloxacin. Gram negative coccobacilli were highly sensitive to chloramphenicol, trimethoprim, gentamicin, Enrofloxacin, Cefotaxime and ciprofloxacin. The pH and chloride levels of the affected quarter milk in subclinical and clinical mastitis cases before the treatment showed significant increase compared to the nonaffected quarter milk values. These values showed significant decrease to normal level on post treatment.